1999
DOI: 10.1111/j.1553-2712.1999.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Acuity on Preference for Information and Autonomy in Decision Making

Abstract: Abstract. Objectives:To test the hypotheses that ED patients' desires for medical information and for autonomy in decision making are inversely related to increasing acuity of illness, increasing age, and lower level of formal education. Methods: The authors conducted a prospective study of ED patients who presented for care during seven nonconsecutive 24-hour periods. Of 804 patients approached, 665 completed a questionnaire that was administered by a trained research assistant. Patients rated their desire fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
(13 reference statements)
3
36
0
Order By: Relevance
“…2,[28][29][30] Prior ED studies have shown that almost all patients express a strong desire to receive medical information, irrespective of acuity, and be actively involved in decision-making. 22,31,32 Given the contrast between the existing literature and the perceptions of our respondents, future research is needed to assess the reasons for this disconnect and to evaluate ways to bridge this knowledge gap. Qualitative studies of ED patients could further assess to what extent, and in what manner, patients want to be involved in emergency care decisions.…”
Section: Discussionmentioning
confidence: 99%
“…2,[28][29][30] Prior ED studies have shown that almost all patients express a strong desire to receive medical information, irrespective of acuity, and be actively involved in decision-making. 22,31,32 Given the contrast between the existing literature and the perceptions of our respondents, future research is needed to assess the reasons for this disconnect and to evaluate ways to bridge this knowledge gap. Qualitative studies of ED patients could further assess to what extent, and in what manner, patients want to be involved in emergency care decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Increased involvement of ED patients in a shared decision-making process has in fact been shown to improve patient satisfaction and decrease utilization without causing patient harm. 63,64 Prior studies have found that almost all ED patients express a strong desire to receive medical information irrespective of acuity, 65 but it remains unclear if EPs feel this tool could be routinely incorporated into their practice and if this would actually result in decreased health care costs. 66 Future studies should further evaluate ways to appropriately incorporate shared decision-making in emergency care with the goal of reducing overuse.…”
Section: Discussionmentioning
confidence: 99%
“…Preferences for involvement in medical decision making can vary according to the situation (Say, Murtagh, & Thomson, 2006). For example, members of the public express more interest in being involved in disease prevention decisions such as smoking cessation and lifestyle change (Mansell, Poses, Kazis, & Duefield, 2000) but prefer to be more passive in situations with more immediate consequences (e.g., cancer treatment; Chewning et al, 2012;Davis, Hoffman, & Hsu, 1999). Yet these generalizations are not universal, and research investigating variation across decision types is needed (Mansell et al, 2000;Waller et al, 2012).…”
mentioning
confidence: 99%